Clinical significance of blood supply to the internal capsule and basal ganglia. (March 2016) - Djulejić, Vuk; Marinković, Slobodan; Georgievski, Biljana; Stijak, Lazar; Aksić, Milan; Puškaš, Laslo; Milić, Ivan
Highlights: The internal capsule and basal ganglia are supplied by the perforating arteries. The upper part of these structures is perfused by the perforators of the middle cerebral artery. The lower and anterior part is perfused by the perforators of the anterior cerebral artery. The lower and posterior part is perfused by the perforators of the anterior choroidal artery. The genu of the capsule is perfused by the perforators of the internal carotid and anterior choroidal arteries. Abstract: Although the general vascular supply of the basal ganglia and internal capsule is well known, precise data are lacking regarding the variations of the vascular territories in the two regions. Twelve hemispheres were studied following an injection of coloured ink into the main cerebral arteries, namely the anterior cerebral (ACA), middle cerebral (MCA), anterior choroidal (AChA) and posterior cerebral artery (PCA). Serial sections of the injected hemispheres were taken in the axial or coronal plane. In 75% of the hemispheres, ACA perforators were seen to supply the inferomedial part of the head of the caudate nucleus and the anterior limb of the internal capsule, as well as the anterior and inferior portions of the putamen and globus pallidus. The MCA vessels perfused the superolateral part of the head and body of the caudate nucleus, the superior part of the entire internal capsule, most of the putamen and part of the globus pallidus. The AChA perforators perfused the medial segment of the globus pallidus, the inferior part of the posterior limb, the retrolenticular and sublenticular portions of the internal capsule, and occasionally its genu. The same segment of the globus pallidus and the inferior part of the genu of the internal capsule were most likely supplied by the perforators of the internal carotid artery. A predominance of ACA territory was noticed in one specimen (8.33%) and a predominance of MCA territory in two specimens (16.67%). The obtained anatomical data may help radiologic determination of perforators involved in ischemic events, as well as a better understanding of the neurological deficits in the same events.